ChemInform Abstract: Polynuclear Heterometallic Complexes from Metal Powders: The "Direct Synthesis" Approach. Issue 45 (23rd October 2014) - Nesterov, Dmytro S.; Nesterova, Oksana V.; Kokozay, Vladimir N.; Pombeiro, Armando J. L.
Abstract Review: [51 refs.